Coagulation and the Vessel Wall in Pulmonary Embolism. (1st December 2013) - Alias, Sherin; Lang, Irene M.
Abstract : Venous thromboembolism comprises deep‐vein thrombosis, thrombus in transit, acute pulmonary embolism, and chronic thromboembolic pulmonary hypertension (CTEPH). Pulmonary thromboemboli commonly resolve, with restoration of normal pulmonary hemodynamics. When they fail to resorb, permanent occlusion of the deep veins and/or CTEPH are the consequences. Apart from endogenous fibrinolysis, venous thrombi resolve by a process of mechanical fragmentation, through organization of the thromboembolus by invasion of endothelial cells, leukocytes, and fibroblasts leading to recanalization. Recent data utilizing various models have contributed to a better understanding of venous thrombosis and the resolution process that is directed at maintaining vascular patency. This review summarizes the plasmatic and cellular components of venous thrombus formation and resolution.